Pengaruh Pelatihan, Pengalaman Kerja dan Motivasi Kerja terhadap Kinerja Karyawan pada PT BPD Kaltimtara Kantor Cabang Utama Kota Samarinda - Zulfikar; Fatahul Rahman; Febry Veronica Tjong (Jurnal EKSIS, 2023)
ABSTRACT : This study aims to determine the relationship between training, work experience, and work motivation on employee performance at PT BPD Kaltimtara Main Branch Office, Samarinda City. This study uses quantitative data in the form of values or scores for the answers given by respondents to the statements in the questionnaire. Data collection techniques in this study used a questionnaire technique, which was measured by a Likert scale. The data analysis methods used were validity test, reliability test, multiple linear regression analysis test, t test, F test, and R2 test, which were tested with the help of Statistical Product And Service Solution (SPSS Ver. 25). The number of research samples is 100. The results showed that training, work experience, and work motivation had a positive and significant effect on employee performance. Simultaneously, training, work experience, and work motivation have a positive and significant effect on employee performance, with a significance value of 0.000 <0.05.